DESIGN PROMOTION MEDIA FOR REOG PONOROGO WITH GRAPHIC MOTION OF WAYANG KULIT - Ajiprabowo, Gheraldi Waskito; Handriyotopo, Handriyotopo (ARTISTIC : International Journal of Creation and Innovation, 2020)
Reog Ponorogo art is an Indonesian cultural heritage that must be preserved in the mid of current cultural competition nowadays. One of the ways to preserve Reog art is by introducing it to the wider community, especially the younger generation. The purpose of this design is to produce motion graphic media to introduce Reog Ponorogo traditional art. This design uses the 5W+1H approach, with the following stages: 1) reviewing the problems; 2) developing with the relevant questions; 3) developing the answers of those questions; 4) making the right solution. The result of this study shows that the design of Reog Ponorogo motion graphics can be the right media to provide information about Reog art to the public, especially millennial youth. This motion graphic media is quite comprehensive, because it is completed with supporting media such as posters, print ads, merchandise, and Instagram.